An ab initio study of C60 adsorption on the Si(001) surface - Gale, Julian; Hobbs, C; Kantorovich, L (Elsevier Science BV, 2005)
Continuing our previous preliminary ab initio DFT study of the adsorption of a C60 molecule on the clean Si(001) surface [C. Hobbs, L. Kantorovich, Nanotechnology 15 (2004) S1] we present possible configurations that the molecule can adsorb in, on the surface. The binding energies for individual sites (over 20) are calculated within the GGA and LDA approximations, taking into account a BSSE correction due to the localised basis set used. Additional adsorption sites to those found previously are identified and analysed in detail and a hierarchy of the most stable sites is constructed. Upon the adsorption, the molecule forms strong covalent bonds with the surface dimers, whereupon the structure of nearby single and double C?C bonds of the C60 cage undergo substantial reformation. We confirm our previous result that the adsorption energies are greatly reduced within the GGA.2005 Elsevier B.V. All rights reserved.